STUDI LITERATURE: TANAMAN OBAT YANG MEMILIKI POTENSI PENYEMBUHAN UNTUK LUKA TERBUKA YANG TERJADI PADA ANAK - Oashttamadea, Ressa; Sabil, Ukhti Khaula (Iris Journal of Health Information Management, 2024)
The process of a wound occurs, namely that blood will come out through the wound, then blood platelets touch the surface of the wound and then release thrombokinase, assisted by calcium ions, which will convert prothrombin into thrombin. Aim of this research to find out the benefits of medicinal plants that have the potential to heal open wounds that often occur in children, and aims to reveal and convey the types/species of plants used in treating open wounds. Method article review by searching several national and international journal publications via the database: Google Scholar. The keywords used are "Indonesian medicinal plants", and "open wounds". Journals published are in the 2013-2023 range (10 years). Based on the results obtained 5 journals regarding in vivo studies of Indonesian herbal plants taken from the leaves, extracts, and sap used as medicine for healing open wounds, secondary metabolite compounds such as flavonoids, tannins, alkaloids, saponins, phenols, steroids, triterpenoids play a role in providing healing effect on open wounds. Conclusion: Several traditional Indonesian medicinal plants have the potential to heal open wounds. Flavonoids are a type of antioxidant that is widely contained in chocolate. Antioxidants themselves work to ward off free radicals in the body. The part of the plant that is often used as herbal medicine in healing wounds is the leaves.